Customary Law of Inheritance and Migration: Adoption of The Old Regime or Adaptation to The New One? - Dewi Sukarti (Universitas Islam Negeri Jakarta, 2017)
This article is a result of field research about the culture of inheritance of migrating Besemah people in Jakarta. The research questions raised in this article are do migrating Besemah people adopt their customary law of inheritance or do they adapt to the regime prevailed in the Jakarta? This article found that Besemah people living in Jakarta have been adapting to the urban way of inheritance which gives similar share between men and women and gives a strong position to wife. Another important finding is that only a small number of migrating Besemahers still maintain the old value and customs of their region of origin. DOI: 10.15408/ajis.v17i2.6236